Exploring Musical Activities and Their Relationship to Emotional Well-Being in Elderly People across Europe: A Study Protocol - Grau-Sánchez, Jennifer; Foley, Meabh; Hlavová, Renata; Muukkonen, Ilkka; Ojinaga-Alfageme, Olatz; Radukic, Andrijana; Spindler, Melanie; Hundevad, Bodil (Frontiers in Psychology, 2017)
Music is a powerful, pleasurable stimulus that can induce positive feelings and can therefore be used for emotional self-regulation. Musical activities such as listening to music, playing an instrument, singing or dancing are also an important source for social contact, promoting interaction and the sense of belonging with others. Recent evidence has suggested that after retirement, other functions of music, such as self-conceptual processing related to autobiographical memories, become more salient. However, few studies have addressed the meaningfulness of music in the elderly. This study aims to investigate elderly people’s habits and preferences related to music, study the role music plays in their everyday life, and explore the relationship between musical activities and emotional well-being across different countries of Europe. A survey will be administered to elderly people over the age of 65 from six different European countries (Bosnia & Herzegovina, Czech Republic, Finland, Germany, Ireland and the United Kingdom) and to a control group. Participants in both groups will be asked about basic socio-demographic information, habits and preferences in their participation in musical activities and emotional well-being. Overall, the aim of this study is to gain a deeper understanding of the role of music in ageing from a psychological perspective. This advanced knowledge could help develop therapeutic applications, such as musical recreational programs for healthy older people or elderly in residential care, which are able to better meet their emotional and social needs.